Cervicothoracic Junction Fractures Management: An Overview of Literature - Dash, Chinmaya (Indian Journal of Neurotrauma, 2019)
The cervicothoracic junction (CTJ) is a unique area of spine and is the junction between the mobile lordotic cervical spine and the rigid kyphotic thoracic spine. It extends from C6 through T4. The fractures of the CTJ are uncommon and not well known. The article focuses on biomechanics of cervicothoracic region, management strategies of fractures of cervicothoracic region, and reviews pertinent literature.
Keywords: cervicothoracic fracture; cervicothoracic; lower cervical fracture; surgery for cervicothoracic fracture; upper thoracic fracture